How High is Too High? The Diagnostic Value of Absolute Eosinophil Count in Excluding Parasitic Infection - Jessica Bass; Evgenii Filippov; Joseph Kubofcik; Michelle Makiya; Miranda Yu; Lauren Wetzler; JeanAnne Ware; Perla Adames Castillo; Michelle Luera; Thomas Brown; Lori Penrod; Thomas B Nutman; et al. (Clinical Infectious Diseases, 2026)
Abstract Background Whereas most recommendations for evaluation of eosinophilic patients list exclusion of parasitic infections as an initial step, this proves difficult in practice due to the lack of sensitive and specific testing. The aim of the current study was to explore the utility of peak absolute eosinophil count (AEC) and serum IgE in distinguishing parasitic from non-parasitic causes of marked eosinophilia. Methods Patients with peak AEC ≥500/µL enrolled on NIH protocols for suspected parasitic disease or eosinophilia between January 1, 1974 and July 30, 2024 were included in this retrospective chart review. Archived sera were retested with species-specific serologies to clarify parasitic diagnoses when indicated. Results A total of 1,025 patients (907 adults; 118 children) were included, of which 360 were diagnosed with a parasitic infection. Median peak AEC was significantly lower in adults and children with parasitic infections compared to those with non-parasitic diagnoses; only 2 patients with parasitic infections (both children with visceral larva migrans (VLM)) had an AEC >30,000/µL. Receiver operating characteristic (ROC) curve analysis identified an AEC cutoff of 28,680/µL in adults and 59,529 cells/µL in children for exclusion of parasitic infection with near 100% specificity. In adults, parasitic diagnoses decreased and malignancy-associated eosinophilia increased with rising AEC (χ2_trend=84.69, P<0.0001). Serum IgE levels were highly variable across all diagnoses and therefore lack clinical relevance. Conclusion Most parasitic infections are associated with mild or moderate eosinophilia. AEC >30,000/µL is rarely due to parasitic infection and should prompt expedited evaluation for non-infectious causes, particularly malignancy and hypereosinophilic syndromes.